Pemanfaatan Teknologi Informasi dan Komunikasi dalam Pendidikan Karakter di Sekolah Dasar - Nurrochman, Taufik; Murtiyasa, Budi (Lembaga Yasin AlSys, 2023)
The purpose of this research is to find out how to use information and communication technology in character education in elementary schools. This research can help educators understand character education using the use of information and communication technology as an important thing in the development of children's character. This study uses the method of literature study. Information and communication technology is utilized by educators to provide more effective learning in the current new normal era, with ICT-based learning media. Character education is very appropriate if it starts from the elementary school level where elementary school education is the foundation for further education. In order to prepare future generations who do not lose their identity as the Indonesian nation. the use of information and communication technology in character education is an alternative that must be applied in character education in elementary schools.